Ferramenta para diagnóstico de maturidade e apoio na implantação de programas de corporate venture capital - Döll, Luciano Mathias (2024)
The challenge for corporations is to gain access to and adopt, to some extent, technologies with disruptive potential. To achieve this, the speed of changes driven by digital transformation requires them to seek alternative approaches. Among the various strategies suggested by open innovation, one is Corporate Venture Capital (CVC), which involves corporations investing in startups. A corporation's motivations for implementing a CVC program can vary, with financial and strategic goals standing out. The objective of this work is to provide a tool that supports corporations in implementing a Corporate Venture Capital program, focusing on identifying critical success indicators and measuring their maturity. This tool assists in conducting a maturity diagnosis based on criteria adopted by the corporation, classified into the following categories: culture and awareness, strategy and objectives, people and dedication, financial capacity, experience and track record, investment thesis, legal and governance. The methodology for this work was carried out in four stages. The first stage involved a review of the state of the art, including academic and market references. The second stage consisted of structuring the criteria and indicators to measure the maturity of a Corporate Venture Capital program. The third stage involved validating the model by applying the adjusted instrument to different CVC programs. The fourth stage entailed making the tool available, which corporations can use as a playbook for structuring a CVC program. This work resulted in a compilation that represents the theory and practice of CVC. A total of 49 critical success factors were identified and classified into seven dimensions: culture and awareness, strategy and objectives, people and dedication, financial capacity, experience and track record, investment thesis, and legal/governance. A web tool (CVCBench) was developed through which corporations interested in implementing a CVC program can measure their maturity regarding these factors. To establish a quality benchmark, this work analyzed four corporations that have already implemented or conducted in-depth studies to implement CVC. The developed web tool allows a corporation to compare its maturity index with the average index observed in these four corporations. Based on this comparison, the tool provides a summary of the corporation’s strengths and weaknesses, thereby serving as a guide to support the corporation in implementing its own Corporate Venture Capital program.